Prognostic factors in stage IB non-small cell lung cancer according to the 8(th) edition of the TNM staging system after curative resection - Moon, Youngkyu (J Thorac Dis, 2019)
BACKGROUND: Patients with stage IB non-small cell lung cancer (NSCLC) with poor prognostic factors can be treated selectively with postoperative adjuvant chemotherapy. The aim of this study was to identify the prognostic factors of stage IB NSCLC according to the new 8(th) edition of the tumor, node, and metastasis (TNM) staging system. METHODS: From 2005 to 2016, 211 patients who were diagnosed with stage IB NSCLC according to the 8(th) edition of the TNM staging system underwent anatomical pulmonary resection (lobectomy or bilobectomy). We analyzed the outcomes of patients receiving adjuvant chemotherapy. The risk factors for prognosis after surgery were also analyzed for NSCLC stage IB. RESULTS: Differences between the 5-year recurrence-free-survival (RFS) rates (71.4% vs. 60.2%, P=0.173) and the 5-year disease-specific-survival (DSS) rates (88.0% vs. 81.4%, P=0.437) obtained by patients receiving surgical treatment only versus patients receiving both surgery and adjuvant chemotherapy, retrospectively, were not significant. Multivariate analysis was conducted to identify the risk factors for recurrence and cancer-related death. Lymphovascular invasion was an independent risk factor for both recurrence and cancer-related death [hazard ratio (HR) =2.045, P=0.020; HR =3.150, P=0.048, respectively). CONCLUSIONS: Lymphovascular invasion was the only prognostic factor identified in patients with 8(th) edition stage IB NSCLC. Adjuvant chemotherapy was not an effective treatment for patients with stage IB NSCLC. The efficacy of adjuvant chemotherapy for stage IB patients with lymphovascular invasion should be evaluated in a future study.